2019
DOI: 10.5815/ijisa.2019.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective Monkey Algorithm for Drug Design

Abstract: Swarm intelligence algorithms are designed to mimic the natural behaviors of living organisms. The birds, animals and insects exhibit extraordinary problem solving behaviors and intelligence when living in colonies or groups. These unique behaviors form the basis for the design of the Metaheuristic which are helpful in solving several real-life combinatorial optimization problems. Monkey algorithm is developed based on the unique behaviors of monkeys such as mountain and tree climbing, jumping, watching and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The method proposed by Devi et al (2014) used a GA guided by the scalarisation of two objective functions, druglikeness (by Lipinski's Rule of 5 Lipinski ( 2004)) and similarity (by Tanimoto similarity Loving et al (2010)) to a known reference molecule from the e-Drug3D database. The weights of the objectives are set a priori.…”
Section: Aggregation-basedmentioning
confidence: 99%
See 2 more Smart Citations
“…The method proposed by Devi et al (2014) used a GA guided by the scalarisation of two objective functions, druglikeness (by Lipinski's Rule of 5 Lipinski ( 2004)) and similarity (by Tanimoto similarity Loving et al (2010)) to a known reference molecule from the e-Drug3D database. The weights of the objectives are set a priori.…”
Section: Aggregation-basedmentioning
confidence: 99%
“…The MoGADdrug method, introduced in Devi et al ( 2021), is a fragment-based GA that constructs new molecules from a set of chemical fragments and a reference molecule as inputs. Building upon previous work Devi et al (2014), which considered only two fragments (acid and amine), this method incorporates a variable-length representation to construct new solutions considering double amine fragments, thus allowing three fragment types. The objective function is a weighted sum of the oral bio-availability score Lipinski (2004), and the 2D similarity based on the Tanimoto coefficient Brown (2009), with the weights being set a priori.…”
Section: Aggregation-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these two objectives, MOBifi also employed the Veber score Veber et al (2002) as a third objective related to oral bioavailability. In Devi et al (2019) , the authors compared the MoMADrug against the MoGADdrug Devi et al (2021) , which uses a weighted sum of the objectives. Their results showed that MoMADrug could produce a more diverse set of solutions due to its multi-objective nature and its use of Pareto dominance criteria.…”
Section: Applications In De Novo Drug Designmentioning
confidence: 99%
“…In the works of Devi et al (2019Devi et al ( , 2020, two multi-objective methods were explored for dnDD of new drug-like molecules: the monkey algorithm (MoMADrug) Devi et al (2019) and the biofilm algorithm (MOBifi) Devi et al (2020). MoMADrug is inspired by the behavior of monkeys, while MOBifi is inspired by the life cycle of bacteria in a biofilm.…”
Section: Pareto-basedmentioning
confidence: 99%